Antiresorptives overlapping ongoing teriparatide treatment result in additional increases in bone mineral density. (18th December 2012) - Muschitz, Christian; Kocijan, Roland; Fahrleitner‐Pammer, Astrid; Lung, Solveig; Resch, Heinrich
Abstract During teriparatide (TPTD) treatment, high levels of bone formation are accompanied by an increase in bone resorption. The aim of this work was to test if coadministration of raloxifene (RAL) or alendronate (ALN) following 9 months of ongoing TPTD therapy would reopen the anabolic window, thereby exerting additional benefit on bone mineral density (BMD). Postmenopausal women (n = 125) with severe osteoporosis on TPTD treatment for 9 months were randomized into three open‐label groups for a further 9 months: ALN (70 mg/week) in addition to TPTD; RAL (60 mg/d) in addition to TPTD; or no medication in addition to TPTD. Amino‐terminal propeptide of type I procollagen (P1NP) and cross‐linked C‐telopeptide (CTX), and areal and volumetric BMD at the lumbar spine and hip were assessed. During the combination period, P1NP concentrations did not change on TPTD monotherapy (693% ± 371%, p < 0.0001) and decreased in the ALN (360% ± 153%, p < 0.0001) and RAL (482% ± 243%, p < 0.0001) combination groups; whereas CTX did not change on TPTD monotherapy (283% ± 215%, p < 0.0001), decreased to the starting level in the ALN combination group (17% ± 72%, p = 0.39), and remained elevated in the RAL combination group (179% ± 341%, p < 0.0001). The increase in lumbar spine BMD was 5% ± 6.3% in the ALN and 6% ± 5.2% in the RAL combination groups compared with 2.8% ± 9.3% in the TPTD monotherapy group (p = 0.085 and p = 0.033, respectively). The increase of trabecular lumbar spine BMD for both the ALN and RAL combination groups was superior to TPTD monotherapy. Total hip BMD changes were 4% ± 5.3% for the ALN combination group and 1.4% ± 5.1% for the TPTD monotherapy (p = 0.032), and 1.4% ± 3.4% (p = 0.02) for the RAL combination group. With the exception of no differences in the trabecular compartment of femoral neck, volumetric BMD changes in the ALN combination group for all other comparisons were significantly superior to the two other groups. Our data suggest that ALN when added to TPTD 9 months after initiation of TPTD monotherapy results in a more robust increase in BMD, probably due to a reopening of the anabolic window. The clinical relevance of the BMD increase is unknown. © 2013 American Society for Bone and Mineral Research